Production of feed enzymes (phytase and plant cell wall hydrolyzing enzymes) by Mucor indicus MTCC 6333: purification and characterization of phytase - Gulati, H K; Chadha, B S; Saini, H S (Folia microbiologica, 2007)
The production of phytase and associated feed enzymes (phosphatase, xylanase, CMCase, alpha-amylase and beta-glucosidase) was determined in a thermotolerant fungus Mucor indicus MTCC 6333, isolated from composting soil. Solid-substrate culturing on wheat bran and optimizing other culture conditions (C and N sources, level of N, temperature, pH, culture age, inoculum level), increased the yield of phytase from 266 +/- 0.2 to 513 +/- 0.4 nkat/g substrate dry mass. The culture extract also contained 112, 194, 171, 396, and 333 nkat/g substrate of phosphatase, xylanase, CMCase, beta-glucosidase and alpha-amylase activities, respectively. Simple 2-step purification employing anion exchange and gel filtration chromatography resulted in 21.9-fold purified phytase. The optimum pH and temperature were pH 6.0 and 70 degrees C, respectively. The phytase was thermostable under acidic conditions, showing 82% residual activity after exposure to 60 degrees C at pH 3.0 and 5.0 for 2 h, and displayed broad substrate specificity. The Km was 200 nmol/L and v(lim) of 113 nmol/s per mg protein with dodecasodium phytate as substrate. In vitro feed trial with feed enzyme resulted in the release of 1.68 g inorganic P/kg of feed after 6 h of incubation at 37 degrees C.
Keywords: gelová chromatografie; 6-Phytase; fermentace; Substrate Specificity; Temperature; Animal Feed; 6-fytasa; endo-1,4-beta-xylanasy; průmyslová mikrobiologie; teplota; Endo-1,4-beta Xylanases; Mucor; Culture Media; Dietary Fiber; kultivační média; hydrolasy; potravní vláknina; Fermentation; Enzyme Stability; krmivo pro zvířata; substrátová specifita; alpha-Amylases; celulasa; Hydrogen-Ion Concentration; alfa-amylasy; Hydrolases; buněčná stěna; koncentrace vodíkových iontů; Industrial Microbiology; Chromatography, Gel; Cell Wall; stabilita enzymů; Cellulase